Obesity in Latin America, a scoping review of public health prevention strategies and an overview of their impact on obesity prevention. Issue 15 (12th October 2021) - Palacios, Cristina; Magnus, Marcia; Arrieta, Alejandro; Gallardo, Héctor; Tapia, Roberto; Espinal, Carlos
Abstract: Objective: To describe the strategies implemented in seventeen Latin American countries for obesity prevention and to provide an overview of their impact. Design: A thorough search of strategies and their impact was done through an Internet search, governmental webpages, reports and research articles in English, Spanish and Portuguese. Setting: Latin America (not including the Caribbean countries). Participants: Any. Results: The Ministry of Health is the main oversight for obesity prevention, with six countries having a specific structure for this. Regular obesity monitoring occurs in a few countries, and thirteen countries have a national obesity prevention plan. The main regulations being implemented/designed are front-of-package labelling (sixteen countries), school environment (fifteen countries), school nutrition education (nine countries), promotion of physical activity level (nine countries) and sugar-sweetened beverage tax (eight countries). All countries have dietary guidelines. The main community-based programmes being implemented are school meals (seventeen countries), complementary nutrition (eleven countries), nutrition education (fourteen countries), promotion of physical activity (nine countries) and healthy environments (nine countries). Most of these strategies have not been evaluated. The few with positive results have used a coordinated, multi-disciplinary and multi-sector approach, with legislation and executive-level support. Conclusions: Important obesity prevention strategies are being implemented in the seventeen Latin American countries included in the present review. However, few have been evaluated to assess their impact on preventing obesity. This information can help assess that actions can be generalised to other countries within the region and can help inform how to prevent obesity in different settings.